2012
DOI: 10.1016/j.immuni.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Circuits Mediated by Lectin-Glycan Interactions in Autoimmunity and Cancer

Abstract: Numerous regulatory programs have been identified that contribute to the restoration of homeostasis at the conclusion of immune responses and to safeguarding against the detrimental effects of chronic inflammation and autoimmune pathology. Malignant cells may usurp these pathways to create immunosuppressive networks that thwart antitumor responses. Herein we review the role of endogenous lectins (C-type lectins, siglecs, and galectins) and specific N- and O-glycans generated by the coordinated action of glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
308
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(313 citation statements)
references
References 124 publications
1
308
0
4
Order By: Relevance
“…13 Our recent studies revealed that Gal-1 induces microglia deactivation and prevents inflammation-induced neurodegeneration. 20 In the present study, we successfully uncoupled the microglial deactivating effect, which was observed using both WT and monomeric Gal-1 from the neuroregenerative effect, which was verified only when high concentrations of WT Gal-1 were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Our recent studies revealed that Gal-1 induces microglia deactivation and prevents inflammation-induced neurodegeneration. 20 In the present study, we successfully uncoupled the microglial deactivating effect, which was observed using both WT and monomeric Gal-1 from the neuroregenerative effect, which was verified only when high concentrations of WT Gal-1 were used.…”
Section: Discussionmentioning
confidence: 99%
“…This lectin exists in a monomer-dimer equilibrium depending on its relative concentration and biochemical features of different tissues. 13 Within the CNS, Gal-1 controls proliferation of adult neural progenitor cells, 14,15 regulates neurogenesis and promotes functional recovery after stroke. 16 Expression of Gal-1 correlates with the regenerative potential of spinal motoneurons after SCI.…”
mentioning
confidence: 99%
“…It has been shown that the interaction between endogenous glycan-binding proteins and glycosylated receptors is of crucial importance for immunological homeostasis (reviewed in ref. 69 ). Within these processes, galectins emerge as important regulators in several physiological and pathological processes (reviewed in Blidner and Rabinovich).…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%
“…The most common and well-defined form of programmed cell death is apoptosis, which is a physiological cell-suicide pro-gramme that is essential for embryonic development (Campos-Ortega and Hartenstein, 2013), immune-system function (Abbas et al, 2012) and the maintenance of tissue homeostasis (Sonnenberg et al, 2011) in multi-cellular organisms. Deregulation of apoptosis has been implicated in numerous pathological conditions, including neurodegenerative diseases (Radi et al, 2014), autoimmunity and cancer (Rabinovich and Croci, 2012).…”
Section: Introductionmentioning
confidence: 99%